The Past of the City the Prayer of the Author/Scribe: On the Implications of Prayers for Cities in Ketaba Records - Sami Arslan (Tarih Dergisi)
Recent scholarship on manuscripts has emphasized the value of nontextual elements, alongside the text itself, as potential sources for historical reconstruction. While manuscripts serve as primary repositories of knowledge, their non-textual components also play a crucial role in knowledge transmission. Property records, for example, offer valuable insights often absent from traditional historical sources. This article delves into one aspect of telif and istinsah records known as ketaba or ferağ records: the prayer sentences inscribed for the cities where the text was copied or ownership was transferred. This study contends that these prayers not only express well wishes for the city, but also reveal the individual or communal sentiments of the scribe/author. Moreover, they potentially hold traces of historical events, offering an additional avenue for historical inquiry.